Modeling the extracellular matrix in cell migration and morphogenesis: a guide for the curious biologist - Crossley, Rebecca M.; Johnson, Samuel; Tsingos, Erika; Bell, Zoe; Berardi, Massimiliano; Botticelli, Margherita; Braat, Quirine J. S.; Metzcar, John; Ruscone, Marco; Yin, Yuan; Shuttleworth, Robyn (Frontiers in Cell and Developmental Biology, 2024)
The extracellular matrix (ECM) is a highly complex structure through which biochemical and mechanical signals are transmitted. In processes of cell migration, the ECM also acts as a scaffold, providing structural support to cells as well as points of potential attachment. Although the ECM is a well-studied structure, its role in many biological processes remains difficult to investigate comprehensively due to its complexity and structural variation within an organism. In tandem with experiments, mathematical models are helpful in refining and testing hypotheses, generating predictions, and exploring conditions outside the scope of experiments. Such models can be combined and calibrated with in vivo and in vitro data to identify critical cell-ECM interactions that drive developmental and homeostatic processes, or the progression of diseases. In this review, we focus on mathematical and computational models of the ECM in processes such as cell migration including cancer metastasis, and in tissue structure and morphogenesis. By highlighting the predictive power of these models, we aim to help bridge the gap between experimental and computational approaches to studying the ECM and to provide guidance on selecting an appropriate model framework to complement corresponding experimental studies.